The Advanced Bionics High Resolution Mode: stimulation rates up to 5000 pps. - Buechner A; Frohne-Büchner C; Gaertner L; Stoever T; Battmer RD; Lenarz T (Acta Oto-Laryngologica, 2010)
Conclusion: The technology of stimulation rates between 1500 and 5000 pulses per second per channel (pps/ch) brings a benefit for all users. However, the fastest possible rate does not necessarily lead to best hearing performance in each individual subject. Individual optimization of stimulation rate is recommended. Objectives: The aim of this study was to investigate the effect of high stimulation rates on speech perception ability. Subjects and methods: Thirteen subjects with at least 3 months of experience with conventional Clarion speech coding strategies were recruited into cross-over studies. The first study investigated stimulation rates of 1500, 2000 and 3000 pps/ch, the second study investigated rates of 2500 and 5000 pps/ch. Speech perception data were collected for testing in quiet and in competing noise . Results: On average, speech perception performance increased significantly when changing from conventional speech coding strategies to High Resolution Mode. Subjects who preferred continous interleaved sampling (CIS) in standard mode appeared to obtain better results with rates of 2500 or 3000 pps/ch than with 5000 pps/ch. The stimulation rate that led to best performance provided the highest stimulation current efficiency in the majority of subjects.